Effects of Self-regulated Learning, Parental Involvement and Homework on Academic Achievement of School Students - Azizi Yahaya; Ismail Maakip; Peter Voo Su Kiong; Malai Yunus Malai Yusuf; Nor Khairunnisa Binti Awang Ramli (2020)
Purpose The focus of this research is around education specifically academic achievement of year 10 students in Secondary Schools Brunei. The purpose of this research is to explore the effects of self-regulated learning, parental involvement, and homework on the academic achievement of the Year 10 students. Methods The collection of data is hoped to provide invaluable insight for teachers, unit of Guidance and Counseling, parents, students, and individual on the topic concerning the academic achievement of the students and particularly their children. Therefore, measures can be taken to address any issues to improve their academic achievement. Before-hand, a pilot study was carried out to determine the consistency of the questionnaire. The research instrument adopted in this research, for instance, is the questionnaire and it involves 300 students of year 10 in randomly selected government schools in Brunei. All the accumulated data were processed using Statistical Package for the Social Science (SPSS). Multiple regression and MANOVA were used to test the research questions. Results The findings provide evidence that self-regulated learning, parental involvement and homework have significant impact on academic achievement [R²= .047, adjusted R² = .046; F= (3,220= 3.742 p=0.05). The model explained 4.7% of the variance in the students’ academic achievement. The findings also showed that self-regulated learning (F = (1, 222 =21.40, p=0.000) and homework (F=(1, 222 = 5.62, p=0.01) has significant effect on gender, except for parental involvement on students’ academic achievement Conclusions Students’ academic achievement was associated with self-regulated learning, parental involvement, and homework. In addition, gender also plays a role in academic achievement with girls outperformed boys. Given this, these predictors should be considered in developing and designing strategies in assisting to increase students’ achievement. However, more research should be conducted in relation to students’ academic achievement since lack of study regarding the issue, particularly in Brunei Darussalam.